Immune training enhances anti-viral responses and improves outcomes in Pax5 −/+ mice susceptible to chronic infection - Zhe Lu; Olivia Stencel; Wei Liu; Eleni Vasileiou; Haifeng C Xu; Piyush Pandey; Paweł Stachura; Abdelrahman Elwy; Anastassia Tsombal; Ann-Sophie Mai; Franziska Auer; Mina N F Morcos; et al. (EMBO Molecular Medicine)
Abstract Viral infections pose a significant global burden. Host susceptibility to pathogens is determined by many factors including genetic variation that can lead to immunodeficient or dysregulated antiviral immune responses. Pax5 heterozygosity (Pax5 −/+), resulting in reduced PAX5 levels in mice, mimics germline or somatic PAX5 dysregulation contributing to diseases such as childhood B-cell precursor acute lymphoblastic leukemia (B-ALL). In contrast to the well-characterized roles of PAX5 during early B-cell development, little is known about how Pax5 heterozygosity impacts antiviral responses. We infected Pax5 −/+ mice with the noncytopathic Lymphocytic Choriomeningitis Virus (LCMV) and found that infection with the chronic Docile strain resulted in decreased survival of Pax5 −/+ mice. While early adaptive CD8+ T-cell (CTL) immunity was robust in Pax5 −/+ mice, LCMV-specific neutralizing antibody production was compromised leading to impaired long-term viral clearance and a pro-inflammatory milieu in the bone marrow (BM). Here we show that survival outcomes were improved upon prophylactic treatment with the β-glucan immune trainer through induction of heterologous protection against chronic infection. β-Glucan enhanced viral clearance, CTL immunity, neutralizing antibody production and reduced monocyte immunosuppression in multiple LCMV-resident host organs. New insight from this study will help design effective prophylactic treatment strategies against chronic viral infections, particularly in genetically predisposed susceptible hosts.